Pinkalicious : soccer star - Kann, Victoria (I can read book., 2012)
Pinkalicious and her soccer team, the Pinksters, play their first game against the Ravens, but when the ball is kicked off the field, Pinkalicious chases it and is picked up by Goldilicious for a trip around the world.